KESALAHAN WIRING PADA APP TERHADAP kWh METER ANALOG ELEKTRIK 1 PHASE PASCABAYAR - Fachrurrazi Fachrurrazi; Yulisman Yulisman (Ensiklopedia Research and Community Service Review, 2022)
kWh meter is one of the most important parts in distributing electrical energy. Consists of several components which if one of these components is damaged, it will affect the measurement and calculation of the kWh meter. Therefore, it is necessary to have rules that regulate all matters relating to the kWh meter itself. Starting from the feasibility of the material to the installation of the kWh meter in accordance with the applicable Standard Operating Procedures (SOP). The wiring diagram on a kWh meter is the main point in the success of a kWh meter calculation. Wiring that is not in accordance with the procedure will have a fatal impact on the distribution of electrical energy, both to PLN as a provider of electrical energy, as well as to customers as consumers. Broadly speaking, a single phase is divided into two types of electricity meter models: Analog kWh meters and Electric kWh meters. Each of the kWh meters has a difference in distributing electrical energy. The type of postpaid kWh meter is the research material that the author will pour in writing this thesis.  Keywords: kWh meter, Analog, Electric, 1 phase, wiring diagram.